1968
DOI: 10.1128/jb.95.2.310-313.1968
|View full text |Cite
|
Sign up to set email alerts
|

Resolution and Identification of Ribosomes from Mycobacteria

Abstract: Ribosomes were isolated from mycobacteria (BCG) by differential centrifugation by use of a modification of Nirenberg's procedure. Individual components of the ribosomal spectrum were resolved in linear sucrose density gradients. Sedimentation constants of the individual components were determined by analytical ultracentrifugation. Ribosomes from Escherichia coli labeled with '4C-uracil were used as markers for an independent confirmation of the identity of individual peaks. The typical ribosomal spectrum of 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In the present work, extreme care has been exercised in the preparation of ribosomal ma- terials to ensure their intact structure and to separate the ribosomes from cell-free membranes. The pressure chamber was chosen to disrupt the mycobacterium because this method gave good disruption and produced active ribosomal preparations, as confirmed by Ribi et al (27) and Trinka et al (34)(35)(36). Partial purification was accomplished by washing ribosomes in NH4C1 overnight, followed by centrifugation to pellet the ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, extreme care has been exercised in the preparation of ribosomal ma- terials to ensure their intact structure and to separate the ribosomes from cell-free membranes. The pressure chamber was chosen to disrupt the mycobacterium because this method gave good disruption and produced active ribosomal preparations, as confirmed by Ribi et al (27) and Trinka et al (34)(35)(36). Partial purification was accomplished by washing ribosomes in NH4C1 overnight, followed by centrifugation to pellet the ribosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The CR gave 10 immune precipitin arcs and the RNA preparation gave 2 arcs when developed with this antiserum. DISCUSSION Although ribosomes from various mycobacteria (8,25,27,28) have been isolated, it was only recently reported that ribosomes or ribosomal protein was tested for the ability to provoke delayed hypersensitivity reactions. Ribosomal protein from BCG (16) and ribosomes or ribosomal subunits from BCG and M. smegmatis have been shown to contain antigens capable of provoking delayed skin reactions in sensitized animals (1).…”
Section: -_ _ _mentioning
confidence: 99%